Sheikh Nawawi Al-Jawi’s Sufism Thoughts of The Book Marăqil ‘Ubūdyah - Subaidi Subaidi; Slamet Untung; Siti Marpuah; Rahimah Embong; Siti Rosilawati Ramlan (Religia, 2023)
Sufism is one of the sciences in Islam that focuses more on the spiritual realm. Therefore, many Islamic communities study Sufism to improve their spiritual quality. One of the references that can be used to study Sufism is the Book Marăqil 'Ubūdyah. The purpose of this study is to explain Shaykh Nawawi al-Jawi's tasawuf thoughts in the book marăqil 'ubūdiyah. This type of research is library research. The uniqueness of his tasawuf thought is related to three fundamental things, namely: first, a salik when he first enters the world of tasawuf he must strengthen his shari'ah teachings, because according to sheikh Nawai shari'a are some of God's laws ordered by the Messenger to mankind originating from God in the form of obligatory laws, sunnah, haram, makruh and mubah; second, sălik. carry out various obligations, traditions, leave various prohibitions, stay away from excessive things that are permissible, carry out caution such as: wara', riyadhah in the form of literacy, hunger and silence; third, understanding the nature of everything, such as witnessing Allah's asthma' (names), Allah's attributes, witnessing the Essence and secrets of the Qur'an, the secrets of prohibition, permissibility, and some unseen knowledge that cannot be obtained from a person. teacher, but the knowledge is understood from God. In the end, it is hoped that this article can provide readers with a deeper understanding of Syekh Nawawi sl-Jawi's taswuf thoughts which combine sharia, tarekat and essence. Syeikh Nawawi pattern of Sufism is belonging to Sunni